PRODUCTION TECHNOLOGY OF NATIONAL CONFECTIONERY "NOVVOT" (Academia Science Repository, 2023)
Confectionery products are multicomponent food products, ready to use, having a certain predetermined shape, obtained as a result of technological processing of the main types of raw materials - navvta, with or without the addition of food ingredients, food additives and flavorings.